TINGKAT STRES PADA MAHASISWA KEPERAWATAN YANG MENYUSUN SKRIPSI - Wenny Nugrahati Carsita (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2018)
ABSTRACT Students are vulnerable to stress when composing a thesis. The stress on students who compose a thesis if it is not immediately addressed will have an impact on the obstruction of the preparation of the thesis, the decline in academic value, and the graduation not on time. The purpose of this study was to determine the stress level of student who compose thesis. This study used quantitative design with a descriptive approach. Sampling technique used total population counted 63 students. The results showed that 28 respondents (44.4%) experienced severe stress, 25 respondents (39.4%) experienced moderate stress, and 10 respondents (15.9%) experienced mild stress. The conclusions in this study indicate that as many as 44.4% of students composing a thesis experience severe stress. This research is expected to become information for educational institutions in an effort to prevent and carry out handling in dealing with student stress so as to prevent students from passing on time. Keywords: Nursing Students, Thesis, Stress Level